APPLICATION OF ARTIFICIAL INTELLIGENCE IN CLOUD COMPUTING TECHNOLOGIES (Web of Technology: Multidimensional Research Journal, 2025)
Cloud computing technology has revolutionized digital services, allowing users to use large-scale computing resources in a demanded and flexible manner. However, along with these capabilities, it also created problems for resource management, security, and fault tolerance. Artificial intelligence (AI) provides advanced solutions to these problems, making cloud infrastructures more efficient, secure, and reliable. This article thoroughly analyzes resource optimization, fault detection, and cybersecurity enhancement techniques implemented using AI.